Prevalence and adverse outcomes of frailty in older patients with acute myocardial infarction after percutaneous coronary interventions: A systematic review and meta‐analysis. Issue 1 (28th September 2022) - Yu, Qian; Guo, Dawei; Peng, Jianan; Wu, Qifei; Yao, Yonghuan; Ding, Mei; Wang, Jiang
Abstract: Background: The association between frailty and older patients with acute myocardial infarction (AMI) after percutaneous coronary intervention (PCI) is unclear. Therefore, we conducted a systematic review and meta‐analysis to investigate the prevalence of frailty in older patients with AMI following PCI, and determine the relationship between frailty and adverse outcomes in these patients. Hypothesis: Older patients with AMI have a higher prevalence of frailty after PCI, and the frailty in these patients increases the risk of adverse outcomes. Methods: A comprehensive search of the PubMed, Cochrane, Ovid (Medline), Ovid (Embase), and Web of Science databases was performed for articles published until October 2021. A meta‐analysis was performed using stata12.0 software. A random‐effects model was used when I 2 was greater than 50%; otherwise, a fixed‐effects model was used. Results: There were a total of 274, 976 older patients in the included studies. Nine studies investigated the prevalence of frailty in older patients with AMI after PCI, with an overall prevalence of 39% (95% confidence interval [CI]: 18%–60%, p  < .001). Six studies included adverse outcomes of frailty in older patients with AMI after PCI, including all‐cause mortality (hazard ratio [HR] = 2.29, 95% CI: 1.65–3.16, p  = .285), rehospitalization (HR = 2.53, 95% CI: 1.38–4.63), and in‐hospital major bleeding (HR = 1.93, 95% CI: 1.29–2.90, p  = .825). Conclusion: The frailty prevalence is increased in older patients with AMI after PCI, especially in ST‐segment elevation myocardial infarction (STEMI). AMI with frailty after PCI is more likely to be associated with worse clinical outcomes, such as death, bleeding, and rehospitalization.